Diaclean Pera Sterilant disinfectant prevents transmission of Covid-19 in mosques - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 15 July 2021 - The spread of Covid-19 in the country has given awareness to all parties to take additional measures to ensure that the transmission of the virus can be minimised, especially in public places, including mosques in Pahang.